Testing a model: a developmental perspective of adolescent male sexuality. - Smith, Laureen H; Guthrie, Barbara J (Journal for specialists in pediatric nursing : JSPN, 2005)
This study tested a model of adolescent male sexuality and evaluated its usefulness for predicting sexual behaviors among a diverse sample.
Keywords: Adolescent; Adolescent Behavior; Coitus; Factor Analysis, Statistical; Human Development; Humans; Likelihood Functions; Longitudinal Studies; Male; Models, Psychological; Multivariate Analysis; Sexual Behavior; Sexuality; United States